Pilihan Antibiotik Pada Pasien Abses Hepar Piogenik - Mukti, Ilham Ramadhana; Vidananda, I Wayan Bagoes; Rahmaningtyas, Ihzani; Hasanovic, Ilyas; Tsany, Imtiyaz; Suryajana, I Wayan; Napitupulu, Rudi Pandapotan; Fahimi, Mukti (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Pyogenic liver abscess is a dangerous, life-threatening disease with a high mortality rate that requires accurate diagnosis and treatment. The most common symptoms are upper abdominal pain, hepatomegaly, high fever, nausea, and vomiting. Pyogenic liver abscess occurs due to infection from anaerobic bacteria or aerobic bacteria. in the United States the reported annual incidence is 3.6 cases per 100,000 people. But in Taiwan it is 17.6 per 100,000 people. Pyogenic liver abscess sufferers are dominated by men but currently it affects older people more, with the most cases aged 50 to 60 years. The purpose of this study was to know the choice of antibiotics in patients with pyogenic liver abscess. Empiric antibiotics should be initiated immediately upon suspicion of a pyogenic liver abscess tailored to kill all possible bacteria: Gram-negative cocci, gram-positive cocci, and anaerobes. Antibiotic regimens include amoxicillin-clavulanic acid, third-generation cephalosporins combined with aminoglycosides, or piperacillin/tazobactam. In cases of penicillin allergy or antibiotic resistance, fluoroquinolones or carbapenems may be used.